Accurate viscosity measurement of nitrates/nitrites salts for concentrated solar power. (1st November 2016) - Jin, Yuan; Cheng, Jinhui; An, Xuehui; Su, Tao; Zhang, Peng; Li, Zhong
Highlights: An optimized rotational coaxial cylinder viscometer with 2.5% uncertainty was used in this work. Viscosity of Hitec in almost whole temperature range was given, and was reassessed. Viscosity of commercial compositions solar salt were measured. Viscosity of the emerging ternary nitrates was measured in high temperature. Abstract: Hitec (NaNO3 -NaNO2 -KNO3 ) and Solar salt (NaNO3 -KNO3 ) are two of molten salts extensively used in Concentrated Solar Power (CSP). Viscosity plays an essential role in process of heat transfer for CSP system. However, it has some certain deviation and unsatisfactory errors among different reports; additionally, it still lacks the data close to melting point, which also makes another barrier for their application. In this work, accurate viscosity data of Hitec and Solar salt with 2.5% uncertainty were systematically measured using an optimized rotational coaxial cylinder in a wide temperature range that fill in the blanks of the existing data. Meanwhile, relevant viscosity were explicitly summarized and particularly analyzed based on the experimental data. Viscosity of the specific components of emerging ternary nitrates (Ca(NO3 )2 -NaNO3 -KNO3, LiNO3 -NaNO3 -KNO3 and Ca(NO3 )2 -LiNO3 -KNO3 mixtures) having potential applications for CSP systems were measured in the high temperature areas for the first time.